Keterampilan Dosen Model Matematika dan Hasil Belajar Mahasiswa dalam Praktik Lesson Study - Zul Jalali Wal Ikram; Najmawati Azis (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2021)
This research aims to describe the skill of mathematics model lecturer and the learning achievement of undergraduate students in lesson study practice. Lesson study activities consist of three phases, namely, planning (plan), teaching and learning practice (do), and observation and reflection (see). Reflection is a crucial phase in Lesson Study activity, since it determines the next step needed for improvement. Reflection activities require teaching skills of the model lecturers. The data was collected in line with the ongoing activities in the Field Work Practices involving 3 mathematics model lecturers and 36 undergraduate students, academic year of 2017 offering C Mathematics Education, Universitas Negeri Malang (Malang State University). The research result shows that (1) The model lecturer teaching skills develops along with lesson study practice; (2) lesson study practice supports model lecturers in developing teaching and learning, as well as improving students' learning achivements.